TOPCon structure solar cell silver paste and its application

By using the combination of components such as silver-covered copper powder, graphite microspheres, glass powder and hydroxyl-containing polyurethane in TOPCon solar cell silver paste, combined with the combined use of aqueous and oily solvents, the existing conductive paste pass-through performance has been solved. The problems of poor and low conductivity have achieved high conductivity and excellent grid-through performance, and are suitable for the production of TOPCon solar cells.

CN114974657BActive Publication Date: 2025-01-14DK ELECTRONICS MATERIALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210661032.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-13
Publication Date
2025-01-14
Estimated Expiration
2042-06-13

AI Technical Summary

Technical Problem

The conductive paste produced by existing domestic conductive paste manufacturers specifically used in TOPCon solar cells has technical defects such as poor grid performance and low conductivity, and it is urgent to develop a new conductive paste.

Method used

75-85 parts of silver-clad copper powder, 10-16 parts of graphite microspheres, 12-20 parts of glass powder, 24-30 parts of hydroxyl-containing polyurethane, 20-25 parts of aqueous solvent, 22-30 parts of oily solvent, 2- A combination of 10 parts of thixotropic agent, 6-16 parts of thickening agent, and 3-9 parts of surfactant, enhances the bonding effect of silver-covered copper powder powder by combining the hydroxyl-containing polyurethane, aqueous solvent and oily solvent. and silver paste cross-interface performance.

Benefits of technology

It significantly improves the grid-through performance and conductivity of the silver paste of TOPCon structure solar cells, reduces production costs, and is suitable for the production of TOPCon solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003690457130000141
    Figure BDA0003690457130000141
Patent Text Reader

Abstract

The present invention belongs to the technical field of solar cells, and particularly relates to a TOPCon structure solar cell silver paste, which comprises the following components by mass: 75-85 parts of silver-coated copper powder, 10-16 parts of graphite microspheres, 12-20 parts of glass powder, 24-30 parts of hydroxyl-containing polyurethane, 20-25 parts of aqueous solvent, 22-30 parts of oily solvent, 2-10 parts of thixotropic agent, 6-16 parts of thickener, 3-9 parts of surfactant; in the hydroxyl-containing polyurethane, the content of hydroxyl is 16-32wt%. The present invention also relates to the use of the TOPCon structure solar cell silver paste as a TOPCon cell front slurry. The TOPCon structure solar cell silver paste exhibits excellent mesh performance and high conductivity, and therefore has broad application prospects and market potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to a TOPCon structure solar cell silver paste, and also relates to use of the TOPCon structure solar cell silver paste as a TOPCon cell front paste. Background Art

[0002] When sunlight shines on the semiconductor pn junction, new hole-electron pairs are formed. Under the action of the built-in electric field of the pn junction, the photogenerated holes flow to the p region and the photogenerated electrons flow to the n region. When the circuit is connected, current is generated. This is the working principle of the photovoltaic effect solar cell. Based on this principle, various solar cells have been developed, produced and applied.

[0003] Among them, the tunnel oxide passivated contact solar cell (TOPCon solar cell) is a solar cell that uses an ultra-thin oxide layer as a passivation layer structure. In 2013, Dr. Frank Feldmann of the Fraunhofer Institute in Germany first reported the concept of the tunnel oxide passivated contact cell.

[0004] The back of the tunneling oxide passivation contact solar cell has an ultra-thin tunneling oxide layer and a highly doped polysilicon thin layer, which together form a passivation contact structure. This structure provides good surface passivation for the back of the silicon wafer. The ultra-thin oxide layer allows majority electrons to tunnel into the polysilicon layer while blocking the recombination of minority holes. Then, electrons are transmitted laterally in the polysilicon layer and collected by the metal, thereby greatly reducing the metal contact recombination current and improving the open circuit voltage and short circuit current of the battery.

[0005] Usually, the substrate of tunneling oxide passivation contact solar cells is mainly N-type silicon substrate, and an ultra-thin oxide layer and doped thin film silicon are used to passivate the back of the cell. The back oxide layer is 1.4nm thick and is grown by wet chemical method. Subsequently, 20nm phosphorus-doped amorphous silicon is deposited on the oxide layer, which is then annealed, recrystallized and the passivation effect is enhanced.

[0006] Research shows that the advantages of tunnel oxide passivation contact solar cells include: (1) excellent interface passivation capability; (2) effective doping to separate the Fermi level in the silicon substrate (high Voc); (3) strong multi-carrier transport capability. Compared with HIT solar cells, the advantages of tunnel oxide passivation contact solar cells include: (1) reduced parasitic absorption loss of light; (2) reduced Si film resistance and lower defect state density; (3) reduced contact resistance of Si / TCO.

[0007] Through research, it was found that the conductive paste produced by existing domestic conductive paste manufacturers for TOPCon solar cells has many technical defects such as poor grid performance and low conductivity. Therefore, it is urgent to develop a new conductive paste that is suitable for TOPCon solar cells. Summary of the invention

[0008] The technical solution disclosed in this application aims to provide a new conductive paste, which exhibits high conductivity and excellent grid-passing performance, and is therefore particularly suitable for the production of TOPCon solar cells, thereby meeting market demand.

[0009] To achieve the above object, the present invention adopts the following technical solutions:

[0010] The first aspect of the present invention provides a TOPCon structure solar cell silver paste, which comprises the following components, in parts by mass: 75-85 parts of silver-coated copper powder, 10-16 parts of graphite microspheres, 12-20 parts of glass powder, 24-30 parts of hydroxyl-containing polyurethane, 20-25 parts of aqueous solvent, 22-30 parts of oily solvent, 2-10 parts of thixotropic agent, 6-16 parts of thickener, and 3-9 parts of surfactant;

[0011] Wherein, the content of hydroxyl groups in the hydroxyl-containing polyurethane is 16 to 32 wt%;

[0012] In addition, the median particle size of the silver-coated copper powder is 90-110 nm, and the median particle size of the graphite microspheres is 50-80 nm.

[0013] It is worth noting that the silver-coated copper powder and graphite microspheres are both commercially available products, and they are all spherical. The use of silver-coated copper powder avoids the use of pure silver powder, thereby reducing the production cost of the TOPCon structure solar cell silver paste.

[0014] The addition of graphite microspheres also reduces the total amount of silver used, which helps to reduce the production cost of the silver paste for the TOPCon structure solar cell while ensuring the conductivity.

[0015] And, preferably, in the hydroxyl-containing polyurethane, the content of hydroxyl is 19-24wt%; more preferably, the content of hydroxyl is 20-24wt%; further preferably, the content of hydroxyl is 22wt%.

[0016] Preferably, in the above-mentioned TOPCon structure solar cell silver paste, the glass powder contains the following components, by mass: 35-55 parts of SiO2, 6-12 parts of TiO2, 8-14 parts of ZnO, 8-14 parts of MgO, 10-20 parts of CaO, 12-18 parts of BaO, and 15-20 parts of Cr2O3.

[0017] In addition, it is worth noting that the glass powder can be sintered in any known suitable preparation steps, which will not be described in detail herein. Exemplarily, the glass powder can be prepared according to the following steps:

[0018] S1: Weigh each component according to the above mass ratio, mix them evenly, and obtain a mixture;

[0019] S2: heating the mixture to 700-860°C and melting at this temperature for 1.5-3 hours to obtain a glass melt;

[0020] S3: cold rolling the molten glass on a double-roll mill to obtain a glass sheet;

[0021] S4: coarsely crushing the glass sheets to obtain coarse glass powder;

[0022] S5: The coarse glass powder is finely crushed to prepare the above-mentioned glass powder.

[0023] Preferably, in the above-mentioned TOPCon structure solar cell silver paste, the aqueous solvent is selected from any one or more combinations of the following: water, methanol, ethanol, n-propanol, isopropanol.

[0024] Further preferably, in the above-mentioned TOPCon structure solar cell silver paste, the aqueous solvent is ethanol.

[0025] Further preferably, in the above-mentioned TOPCon structure solar cell silver paste, the aqueous solvent is a combination of ethanol and n-propanol.

[0026] Further preferably, in the above-mentioned TOPCon structure solar cell silver paste, the aqueous solvent is a combination of water and methanol.

[0027] Preferably, in the above-mentioned TOPCon structure solar cell silver paste, the oily solvent is selected from any one or more of the following combinations: dioctyl phthalate, dimethyl adipate, dimethyl glutarate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,4-trimethylpentanediol isobutyl ester, benzyl benzoate, ethylene glycol phenyl ether, propylene glycol phenyl ether, ethylene glycol phenyl ether acetate, propylene glycol phenyl ether acetate, butyl carbitol, butyl carbitol acetate, dibutyl phthalate, and pineneol.

[0028] Further preferably, in the above-mentioned TOPCon structure solar cell silver paste, the oily solvent consists of 2,2,4-trimethylpentanediol isobutyl ester, dibutyl phthalate and pinene alcohol.

[0029] More preferably, the mass ratio of the 2,2,4-trimethylpentanediol isobutyl ester, the dibutyl phthalate and the terpineol is 1:1:1.

[0030] More preferably, the mass ratio of the 2,2,4-trimethylpentanediol isobutyl ester, the dibutyl phthalate and the terpineol is 2:1:1.

[0031] More preferably, the mass ratio of the 2,2,4-trimethylpentanediol isobutyl ester, the dibutyl phthalate and the terpineol is 1:2:1.

[0032] Most preferably, the mass ratio of the 2,2,4-trimethylpentanediol isobutyl ester, the dibutyl phthalate and the terpineol is 1:1:2.

[0033] It is worth mentioning that the inventor unexpectedly found that when the three components of hydroxyl-containing polyurethane + aqueous solvent + oily solvent are used at the same time, the TOPCon structure solar cell silver paste can show excellent mesh performance and high conductivity. The inventor found through analysis that the aqueous solvent + oily solvent composite technology uses a large number of active functional groups (such as -OH), which can enhance the bonding effect between the hydroxyl-containing polyurethane and the silver-coated copper powder. At the same time, the bonding effect between the TOPCon structure solar cell silver paste and the cell substrate is also enhanced. Among them, the oily solvent can lubricate the silver-coated copper powder and reduce the friction between the powders to increase the arrangement density and stacking density of the powder in the silver grid line after sintering and curing, and also weaken the friction between the silver paste and the screen during printing, thereby improving and improving the fine grid and high-speed printing of the silver paste. Among them, the aqueous solvent can improve the compatibility and wettability of the silver-coated copper powder with the hydroxyl-containing polyurethane, and give the silver paste a lower viscosity and better fluidity, so that the silver paste has excellent mesh performance and long-term usability.

[0034] In summary, the inventors believe through analysis that this may be because hydrogen bonds are formed between the hydroxyl-containing polyurethane, aqueous solvent, and oily solvent, and the hydrogen bonds are also connected to the battery cell substrate, thereby ultimately achieving higher conductivity.

[0035] Preferably, in the above-mentioned TOPCon structure solar cell silver paste, the thixotropic agent is selected from any one or more combinations of the following: polyamide wax, polyethylene wax, hydrogenated castor oil, Span 80, Span 60, hexadecanol.

[0036] Preferably, in the above-mentioned TOPCon structure solar cell silver paste, the thickener is selected from any one or more combinations of the following: acrylic resin, ethyl cellulose, hibiscus gum.

[0037] Preferably, in the above-mentioned TOPCon structure solar cell silver paste, the surfactant is selected from any one or more combinations of the following: anionic surfactants, cationic surfactants, zwitterionic surfactants, and nonionic surfactants.

[0038] Further preferably, the anionic surfactant may be selected from one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and stearic acid.

[0039] Further preferably, the cationic surfactant may be a quaternary ammonium compound.

[0040] Further preferably, the zwitterionic surfactant may be selected from one or more of amino acid type zwitterionic surfactants, betaine type zwitterionic surfactants, polyacrylamide and lecithin.

[0041] Further preferably, the nonionic surfactant may be selected from one or more of sorbitan fatty acid, glycerol fatty acid ester and polysorbate.

[0042] In addition, the second aspect of the present invention provides a method for preparing the silver paste of the TOPCon structure solar cell according to the first aspect, comprising the following steps:

[0043] P1: At room temperature, weigh silver-coated copper powder, graphite microspheres and glass powder, mix them to obtain a premix a;

[0044] P2: Weigh hydroxyl-containing polyurethane, aqueous solvent, oily solvent, thixotropic agent, thickener and surfactant, heat while stirring until the hydroxyl-containing polyurethane is completely dissolved, continue stirring evenly, and then cool to room temperature to obtain premix b;

[0045] P3: Add premix a to premix b, stir evenly, grind and disperse, and obtain the TOPCon structure solar cell silver paste.

[0046] In the above preparation method, each operation step is a conventional operation; for example, operations such as mixing, stirring, heating, and grinding are conventional operations known to those skilled in the art, and therefore will not be described in detail herein.

[0047] In addition, the third aspect of the present invention provides the use of the TOPCon structure solar cell silver paste described in the first aspect as a TOPCon cell front paste.

[0048] In summary, compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects:

[0049] The combined use of silver-coated copper powder and graphite microspheres significantly reduces the agglomeration phenomenon between particles, which is conducive to improving the mesh performance of the conductive paste; in particular, the combined use of the three components of hydroxyl-containing polyurethane + aqueous solvent + oily solvent not only improves the mesh performance of the TOPCon structure solar cell silver paste, but also significantly improves the conductivity. Therefore, the TOPCon structure solar cell silver paste provided by the present invention exhibits excellent mesh performance and high conductivity, and therefore has broad application prospects and market potential. DETAILED DESCRIPTION

[0050] The present invention is described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] According to the technical solution provided in the first aspect of the present invention, a TOPCon structure solar cell silver paste comprises the following components, measured by mass: 75 parts of silver-coated copper powder, 12 parts of graphite microspheres, 14 parts of glass powder, 24 parts of hydroxyl-containing polyurethane, 20 parts of aqueous solvent, 22 parts of oily solvent, 3 parts of thixotropic agent, 8 parts of thickener, and 4 parts of surfactant;

[0052] Wherein, the content of hydroxyl in the hydroxyl-containing polyurethane is 20-24wt%;

[0053] In addition, the median particle size of the silver-coated copper powder is 90 nm, and the median particle size of the graphite microspheres is 60 nm.

[0054] In a preferred embodiment, a TOPCon structure solar cell silver paste comprises the following components, by mass: 80 parts of silver-coated copper powder, 14 parts of graphite microspheres, 16 parts of glass powder, 27 parts of hydroxyl-containing polyurethane, 24 parts of aqueous solvent, 26 parts of oily solvent, 6 parts of thixotropic agent, 12 parts of thickener, and 7 parts of surfactant;

[0055] Wherein, the content of hydroxyl in the hydroxyl-containing polyurethane is 20-24wt%;

[0056] In addition, the median particle size of the silver-coated copper powder is 90 nm, and the median particle size of the graphite microspheres is 60 nm.

[0057] In a preferred embodiment, a TOPCon structure solar cell silver paste comprises the following components, by mass: 85 parts of silver-coated copper powder, 16 parts of graphite microspheres, 16 parts of glass powder, 27 parts of hydroxyl-containing polyurethane, 24 parts of aqueous solvent, 26 parts of oily solvent, 6 parts of thixotropic agent, 12 parts of thickener, and 7 parts of surfactant;

[0058] Wherein, the content of hydroxyl in the hydroxyl-containing polyurethane is 22wt%;

[0059] In addition, the median particle size of the silver-coated copper powder is 90 nm, and the median particle size of the graphite microspheres is 60 nm.

[0060] In some preferred embodiments, the glass powder comprises the following components, in parts by mass: 35-55 parts of SiO2, 6-12 parts of TiO2, 8-14 parts of ZnO, 8-14 parts of MgO, 10-20 parts of CaO, 12-18 parts of BaO, and 15-20 parts of Cr2O3.

[0061] In a preferred embodiment, the glass powder is prepared according to the following steps:

[0062] S1: Weigh each component according to the above mass ratio, mix them evenly, and obtain a mixture;

[0063] S2: heating the mixture to 700-860°C and melting at this temperature for 1.5-3 hours to obtain a glass melt;

[0064] S3: cold rolling the molten glass on a double-roll mill to obtain a glass sheet;

[0065] S4: coarsely crushing the glass sheets to obtain coarse glass powder;

[0066] S5: The coarse glass powder is finely crushed to prepare the glass powder.

[0067] In some preferred embodiments, the aqueous solvent is selected from any one or more combinations of the following: water, methanol, ethanol, n-propanol, isopropanol.

[0068] In a preferred embodiment, the aqueous solvent is ethanol.

[0069] In another preferred embodiment, the aqueous solvent is a combination of ethanol and n-propanol.

[0070] In yet another preferred embodiment, the aqueous solvent is a combination of water and methanol.

[0071] In some preferred embodiments, the oily solvent is selected from any one or more combinations of the following: dioctyl phthalate, dimethyl adipate, dimethyl glutarate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,4-trimethylpentanediol isobutyl ester, benzyl benzoate, ethylene glycol phenyl ether, propylene glycol phenyl ether, ethylene glycol phenyl ether acetate, propylene glycol phenyl ether acetate, butyl carbitol, butyl carbitol acetate, dibutyl phthalate, and terpineol.

[0072] In a further preferred embodiment, the oily solvent consists of 2,2,4-trimethylpentanediol isobutyl ester, dibutyl phthalate and terpineol.

[0073] In a further preferred embodiment, the mass ratio of the 2,2,4-trimethylpentanediol isobutyl ester, the dibutyl phthalate and the terpineol is 1:1:1.

[0074] In a further preferred embodiment, the mass ratio of the 2,2,4-trimethylpentanediol isobutyl ester, the dibutyl phthalate and the terpineol is 2:1:1.

[0075] In a further preferred embodiment, the mass ratio of the 2,2,4-trimethylpentanediol isobutyl ester, the dibutyl phthalate and the terpineol is 1:2:1.

[0076] In a most preferred embodiment, the mass ratio of the 2,2,4-trimethylpentanediol isobutyl ester, the dibutyl phthalate and the terpineol is 1:1:2.

[0077] In some preferred embodiments, the thixotropic agent is selected from any one or more combinations of the following: polyamide wax, polyethylene wax, hydrogenated castor oil, Span 80, Span 60, and hexadecanol.

[0078] In some preferred embodiments, the thickener is selected from any one or more combinations of the following: acrylic resin, ethyl cellulose, and hibiscus gum.

[0079] In some preferred embodiments, the surfactant is selected from any one or more combinations of the following: anionic surfactants, cationic surfactants, zwitterionic surfactants, and nonionic surfactants.

[0080] In a further preferred embodiment, the anionic surfactant is sodium dodecylbenzene sulfonate.

[0081] In a further preferred embodiment, the cationic surfactant is a quaternary ammonium compound.

[0082] In a further preferred embodiment, the zwitterionic surfactant is an amino acid type zwitterionic surfactant.

[0083] In a further preferred embodiment, the zwitterionic surfactant is a betaine-type zwitterionic surfactant.

[0084] In a further preferred embodiment, the nonionic surfactant is the fatty acid sorbitan.

[0085] According to the technical solution provided in the second aspect of the present invention, the TOPCon structure solar cell silver paste described in the first aspect is prepared according to the following steps:

[0086] P1: At room temperature, weigh silver-coated copper powder, graphite microspheres and glass powder, mix them to obtain a premix a;

[0087] P2: Weigh hydroxyl-containing polyurethane, aqueous solvent, oily solvent, thixotropic agent, thickener and surfactant, heat while stirring until the hydroxyl-containing polyurethane is completely dissolved, continue stirring evenly, and then cool to room temperature to obtain premix b;

[0088] P3: Add premix a to premix b, stir evenly, grind and disperse, and obtain the TOPCon structure solar cell silver paste.

[0089] In addition, the third aspect of the present invention provides the use of the TOPCon structure solar cell silver paste described in the first aspect as a TOPCon cell front paste.

[0090] The present invention is described in detail and specifically by specific examples below to provide a better understanding of the present invention, but the following examples do not limit the scope of the present invention.

[0091] Example 1

[0092] Prepare TOPCon structure solar cell silver paste I in the following steps:

[0093] P1: At room temperature, weigh silver-coated copper powder, graphite microspheres and glass powder, mix them to obtain a premix a;

[0094] P2: Weigh hydroxyl-containing polyurethane, aqueous solvent, oily solvent, thixotropic agent, thickener and surfactant, heat while stirring until the hydroxyl-containing polyurethane is completely dissolved, continue stirring evenly, and then cool to room temperature to obtain premix b;

[0095] P3: Add premix a to premix b, stir evenly, grind and disperse, and obtain TOPCon structure solar cell silver paste I.

[0096] Among them, by mass, 80 parts of silver-coated copper powder, 13 parts of graphite microspheres, 16 parts of glass powder, 26 parts of hydroxyl-containing polyurethane, 24 parts of aqueous solvent, 28 parts of oily solvent, 7 parts of thixotropic agent, 12 parts of thickener, and 5 parts of surfactant; the median particle size of the silver-coated copper powder is 100nm, and the median particle size of the graphite microspheres is 70nm;

[0097] Wherein, the glass powder comprises the following components, by mass: 48 parts of SiO2, 11 parts of TiO2, 12 parts of ZnO, 13 parts of MgO, 15 parts of CaO, 16 parts of BaO, and 19 parts of Cr2O3;

[0098] The aqueous solvent is a combination of ethanol and n-propanol (volume ratio 1:1); the oily solvent is composed of 2,2,4-trimethylpentanediol isobutyl ester, dibutyl phthalate and terpineol (mass ratio 1:1:1);

[0099] Wherein, the thixotropic agent is polyethylene wax, the thickener is hibiscus gum, and the surfactant is sodium dodecylbenzene sulfonate;

[0100] Wherein, the content of hydroxyl groups in the hydroxyl-containing polyurethane is 20wt%.

[0101] Example 2

[0102] In this embodiment, the mass ratio of 2,2,4-trimethylpentanediol isobutyl ester, dibutyl phthalate and pinene alcohol is 2:1:1; other than this, the preparation steps and the types and proportions of the components are the same as those in Example 1, and finally TOPCon structure solar cell silver paste II is obtained.

[0103] Example 3

[0104] In this embodiment, the mass ratio of 2,2,4-trimethylpentanediol isobutyl ester, dibutyl phthalate and pinene alcohol is 1:2:1; other than this, the preparation steps and the types and proportions of the components are the same as those in Example 1, and finally TOPCon structure solar cell silver paste III is obtained.

[0105] Example 4

[0106] In this embodiment, the mass ratio of 2,2,4-trimethylpentanediol isobutyl ester, dibutyl phthalate and pinene alcohol is 1:1:2; other than this, the preparation steps and the types and proportions of the components are the same as those in Example 1, and finally TOPCon structure solar cell silver paste IV is obtained.

[0107] Example 5

[0108] In this embodiment, the hydroxyl content of the hydroxyl-containing polyurethane is 21 wt %; otherwise, the preparation steps and the types and proportions of the components are the same as those in Example 4, and finally TOPCon structure solar cell silver paste V is obtained.

[0109] Example 6

[0110] In this embodiment, the hydroxyl content of the hydroxyl-containing polyurethane is 22 wt %; otherwise, the preparation steps and the types and proportions of the components are the same as those in Example 4, and finally TOPCon structure solar cell silver paste VI is obtained.

[0111] Example 7

[0112] In this embodiment, the hydroxyl content of the hydroxyl-containing polyurethane is 23 wt %; other than this, the preparation steps and the types and proportions of the components are the same as those in Example 4, and finally TOPCon structure solar cell silver paste VII is obtained.

[0113] Example 8

[0114] In this embodiment, the hydroxyl content of the hydroxyl-containing polyurethane is 24 wt %; otherwise, the preparation steps and the types and proportions of the components are the same as those in Example 4, and finally TOPCon structure solar cell silver paste VIII is obtained.

[0115] Comparative Example 1

[0116] Prepare silver paste α as follows:

[0117] P1: At room temperature, weigh silver-coated copper powder, graphite microspheres and glass powder, mix them to obtain a premix a;

[0118] P2: Weigh a hydroxyl-free polyurethane, an aqueous solvent, an oily solvent, a thixotropic agent, a thickener and a surfactant, heat while stirring until the hydroxyl-free polyurethane is completely dissolved, continue stirring evenly, and then cool to room temperature to obtain a premix b;

[0119] P3: Add premix a to premix b, stir evenly, grind and disperse to obtain silver paste α.

[0120] Among them, by mass, 80 parts of silver-coated copper powder, 13 parts of graphite microspheres, 16 parts of glass powder, 26 parts of hydroxyl-free polyurethane, 24 parts of aqueous solvent, 28 parts of oily solvent, 7 parts of thixotropic agent, 12 parts of thickener, and 5 parts of surfactant; the median particle size of the silver-coated copper powder is 100nm, and the median particle size of the graphite microspheres is 70nm;

[0121] Wherein, the glass powder comprises the following components, by mass: 48 parts of SiO2, 11 parts of TiO2, 12 parts of ZnO, 13 parts of MgO, 15 parts of CaO, 16 parts of BaO, and 19 parts of Cr2O3;

[0122] The aqueous solvent is a combination of ethanol and n-propanol (volume ratio 1:1); the oily solvent is composed of 2,2,4-trimethylpentanediol isobutyl ester, dibutyl phthalate and terpineol (mass ratio 1:1:2);

[0123] Wherein, the thixotropic agent is polyethylene wax, the thickener is hibiscus gum, and the surfactant is sodium dodecylbenzene sulfonate.

[0124] Comparative Example 2

[0125] Prepare silver paste β as follows:

[0126] P1: At room temperature, weigh silver-coated copper powder, graphite microspheres and glass powder, mix them to obtain a premix a;

[0127] P2: Weigh hydroxyl-containing polyurethane, oily solvent, thixotropic agent, thickener and surfactant, heat while stirring until the hydroxyl-containing polyurethane is completely dissolved, continue stirring evenly, and then cool to room temperature to obtain premix b;

[0128] P3: Add premix a to premix b, stir evenly, grind and disperse to obtain silver paste β.

[0129] Among them, by mass, 80 parts of silver-coated copper powder, 13 parts of graphite microspheres, 16 parts of glass powder, 26 parts of hydroxyl-containing polyurethane, 28 parts of oily solvent, 7 parts of thixotropic agent, 12 parts of thickener, and 5 parts of surfactant; the median particle size of the silver-coated copper powder is 100nm, and the median particle size of the graphite microspheres is 70nm;

[0130] Wherein, the glass powder comprises the following components, by mass: 48 parts of SiO2, 11 parts of TiO2, 12 parts of ZnO, 13 parts of MgO, 15 parts of CaO, 16 parts of BaO, and 19 parts of Cr2O3;

[0131] The oily solvent is composed of 2,2,4-trimethylpentanediol isobutyl ester, dibutyl phthalate and terpineol (mass ratio is 1:1:2);

[0132] Wherein, the thixotropic agent is polyethylene wax, the thickener is hibiscus gum, and the surfactant is sodium dodecylbenzene sulfonate;

[0133] Wherein, the content of hydroxyl groups in the hydroxyl-containing polyurethane is 22 wt%.

[0134] Comparative Example 3

[0135] Prepare silver paste gamma according to the following steps:

[0136] P1: At room temperature, weigh silver-coated copper powder, graphite microspheres and glass powder, mix them to obtain a premix a;

[0137] P2: Weigh hydroxyl-containing polyurethane, aqueous solvent, thixotropic agent, thickener and surfactant, heat while stirring until the hydroxyl-containing polyurethane is completely dissolved, continue stirring evenly, and then cool to room temperature to obtain premix b;

[0138] P3: Add premix a to premix b, stir evenly, grind and disperse to obtain silver paste γ.

[0139] Among them, by mass, 80 parts of silver-coated copper powder, 13 parts of graphite microspheres, 16 parts of glass powder, 26 parts of hydroxyl-containing polyurethane, 24 parts of aqueous solvent, 7 parts of thixotropic agent, 12 parts of thickener, and 5 parts of surfactant; the median particle size of the silver-coated copper powder is 100nm, and the median particle size of the graphite microspheres is 70nm;

[0140] Wherein, the glass powder comprises the following components, by mass: 48 parts of SiO2, 11 parts of TiO2, 12 parts of ZnO, 13 parts of MgO, 15 parts of CaO, 16 parts of BaO, and 19 parts of Cr2O3;

[0141] Wherein, the aqueous solvent is a combination of ethanol and n-propanol (volume ratio 1:1);

[0142] Wherein, the thixotropic agent is polyethylene wax, the thickener is hibiscus gum, and the surfactant is sodium dodecylbenzene sulfonate;

[0143] Wherein, the content of hydroxyl groups in the hydroxyl-containing polyurethane is 22 wt%.

[0144] Comparative Example 4

[0145] Prepare silver paste δ by following the steps below:

[0146] P1: At room temperature, weigh silver-coated copper powder, graphite microspheres and glass powder, mix them to obtain a premix a;

[0147] P2: Weigh hydroxyl-containing polyurethane, aqueous solvent, oily solvent, thixotropic agent, and thickener, heat while stirring until the hydroxyl-containing polyurethane is completely dissolved, continue stirring evenly, and then cool to room temperature to obtain premix b;

[0148] P3: Add premix a to premix b, stir evenly, grind and disperse, and obtain silver paste δ.

[0149] Among them, by mass, 80 parts of silver-coated copper powder, 13 parts of graphite microspheres, 16 parts of glass powder, 26 parts of hydroxyl-containing polyurethane, 24 parts of aqueous solvent, 28 parts of oily solvent, 7 parts of thixotropic agent, and 12 parts of thickener; the median particle size of the silver-coated copper powder is 100nm, and the median particle size of the graphite microspheres is 70nm;

[0150] Wherein, the glass powder comprises the following components, by mass: 48 parts of SiO2, 11 parts of TiO2, 12 parts of ZnO, 13 parts of MgO, 15 parts of CaO, 16 parts of BaO, and 19 parts of Cr2O3;

[0151] The aqueous solvent is a combination of ethanol and n-propanol (volume ratio 1:1); the oily solvent is composed of 2,2,4-trimethylpentanediol isobutyl ester, dibutyl phthalate and terpineol (mass ratio 1:1:2);

[0152] Wherein, the thixotropic agent is polyethylene wax, the thickener is hibiscus gum, and the surfactant is sodium dodecylbenzene sulfonate;

[0153] Wherein, the content of hydroxyl groups in the hydroxyl-containing polyurethane is 22 wt%.

[0154] In addition, the inventors also tested the key indicators of silver pastes I to VIII and silver pastes α to δ of TOPCon structure solar cells:

[0155] The viscosity (Pa.s) of the conductive paste was tested at room temperature 25° C. using a rotational viscometer (52 rotor viscometer). The test results are shown in Table 1 below.

[0156] Screen performance test: The conductive paste (TOPCon structure solar cell silver paste I~VIII, silver paste α~δ) was printed on TOPCon cells of 120mm×110mm×100mm respectively, and a screen with specifications of 12500 mesh-2μm line diameter-3μm line width was selected. The printing was continued for 6 hours, and the blocking and breaking of the network were observed. The test results are shown in Table 1 below.

[0157] In addition, the conductive paste (TOPCon structure solar cell silver paste I to VIII, silver paste α to δ) was printed on the N-type TOPCon crystalline silicon substrate, dried to obtain a film thickness of 15 microns, and sintered at 760 to 780° C. The obtained cell was tested for current-voltage performance. The test results are shown in Table 1 below:

[0158] Table 1

[0159]

[0160] As can be seen from Table 1 above, the combined use of the three components of hydroxyl-containing polyurethane + aqueous solvent + oily solvent not only improves the grid-passing performance of the TOPCon structure solar cell silver paste, but also significantly improves the conductivity (low contact resistance and low volume resistivity).

[0161] In particular, the TOPCon structure solar cell silver paste VI in Table 1 above exhibits the lowest contact resistance and volume resistivity, and has the best grid-through performance, and is therefore particularly suitable for the production of TOPCon structure solar cells.

[0162] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.

Claims

1. A TOPCon structure solar cell silver paste, characterized in that: The invention comprises the following components by weight: 75-85 parts of silver-coated copper powder, 10-16 parts of graphite microspheres, 12-20 parts of glass powder, 24-30 parts of hydroxyl-containing polyurethane, 20-25 parts of aqueous solvent, 22-30 parts of oily solvent, 2-10 parts of thixotropic agent, 6-16 parts of thickener, and 3-9 parts of surfactant; Wherein, the content of hydroxyl in the hydroxyl-containing polyurethane is 16-32wt%; Furthermore, the median particle size of the silver-coated copper powder is 90-110 nm, and the median particle size of the graphite microspheres is 50-80 nm; Wherein, the glass powder comprises the following components, in parts by mass: 35-55 parts of SiO2, 6-12 parts of TiO2, 8-14 parts of ZnO, 8-14 parts of MgO, 10-20 parts of CaO, 12-18 parts of BaO, and 15-20 parts of Cr2O3; The aqueous solvent is selected from any one or more of the following combinations: water, methanol, ethanol, n-propanol, isopropanol; The oily solvent consists of 2,2,4-trimethylpentanediol isobutyl ester, dibutyl phthalate and terpineol; the mass ratio of the 2,2,4-trimethylpentanediol isobutyl ester, the dibutyl phthalate and the terpineol is 1:1:

2.

2. The TOPCon structure solar cell silver paste according to claim 1, characterized in that: The thixotropic agent is selected from any one or more combinations of the following: polyamide wax, polyethylene wax, hydrogenated castor oil, Span 80, Span 60, and hexadecanol.

3. The TOPCon structure solar cell silver paste according to claim 1, characterized in that: The thickener is selected from any one or more combinations of the following: acrylic resin, ethyl cellulose, and hibiscus gum.

4. The TOPCon structure solar cell silver paste according to claim 1, characterized in that: The surfactant is selected from any one or more combinations of the following: anionic surfactants, cationic surfactants, zwitterionic surfactants, and nonionic surfactants.

5. Use of the TOPCon structure solar cell silver paste according to claim 1 as TOPCon cell front paste.

Citation Information

Patent Citations

  • High-performance conductive silver paste

    CN109509568A

  • Low-temperature conductive paste composition, preparation method and application thereof

    CN113963840A